a) If $f: E \to F$ and $g: F \to E \ $ are functions such that $g \circ f$ is injective, then $f$ is injective

b) If $f: E \to F$ and $g: F \to E \ $ are functions such that $g \circ f$ is surjective, then $g$ is surjective.


a) Assume $g \circ f$ is injective but $f$ is not injective. Then there exist $x_1, x_2 \in E$ such that $x_1 \neq x_2$ but $f(x_1) = f(x_2)$. Then $g(f(x_1)) = g(f(x_2))$. Since $g\circ f$ is injective, $x_1 = x_2$, a contradiction! Therefore $f$ is injective.

b) Assume $g \circ f$ is surjective but $g$ is not surjective. Then there exists $e_1 \in E$ such that $e_1 \neq g(z)$ for all $z \in f$. Since $g\circ f$ is surjective, there exists $x_1 \in E$ such that $g(f(x_1)) = e_1$. But this is a contradiction to the hypothesis that $g$ is not surjective, since $f(x_1) = y_1 \in F$! Therefore $g$ is surjective.

Is everything here correct or did I make a mistake somewhere? If anyone has a cleaner proof I'd appreciate it as well, since I have still not convinced myself of the validity of the one I wrote above.


It is okay, but can be done more directly.

Let $f(x_1)=f(x_2)$.

Then $(g\circ f)(x_1)=g(f(x_1))=g(f(x_2))=(g\circ f)(x_2)$ so the injectivity of $g\circ f$ tells us that $x_1=x_2$.

Proved is now that $f$ is injective.

Let $e\in E$.

Since $g\circ f$ is surjective we have $g(f(x))=(g\circ f)(x)=e$ for some $x$.

That means that $g$ must be surjective.


1) Injectivity has been dealt with.

2) Surjectivity:

$f: E \rightarrow F$; $g: F \rightarrow E.$

Show that:

If $g \circ f$ is surjective then $g$ is surjective:

$g\circ f$ : $E \rightarrow E.$

Let $e_2 \in E$, then,

since $g \circ f$ surjective, there is an $e_1 \in E$ such that

$(g\circ f)(e_1)=g(f(e_1))=e_2$, i.e.

there is an element $z= f(e_1) \in F$ with

$g(z)=e_2$, hence surjective.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.